Comparative Efficacy of Oral Pharmaceuticals for the Treatment of Chronic Peripheral Neuropathic Pain: Meta‐Analysis and Indirect Treatment Comparisons. Issue 5 (22nd April 2013) - Ney, John Peter; Devine, Emily Beth; Watanabe, Jonathan H.; Sullivan, Sean D.
Abstract Objective Neuropathic pain is generally chronic and challenging to treat. Studies often ignore chronicity by reporting short‐duration outcomes and fail to account for medication tolerability. We assessed efficacy of oral medications on chronic peripheral neuropathic pain. Methods Relevant published, English‐language, randomized controlled trials administering oral medications for peripheral neuropathic pain were identified through MEDLINE (1966 to Dec 1, 2012), EMBASE (1980 to December 2012), the Cochrane Library Databases (through December 2012), and the Oxford Pain Relief Database (through 2012). Included studies reported end point pain or pain reduction from baseline on an 11‐point scale (0–10); had active treatment ≥ 12 weeks; reported an intention‐to‐treat analysis, and had 5‐point quality score ≥ 3. Abstracted information included patient characteristics, neuropathic pain condition, drug and dosage arms, adverse events rates causing dropout, and secondary measures (50% pain improvement, global improvement, and sleep interference). Primary outcome meta‐analysis, stratified by drug and dosage, was followed by an indirect treatment comparison adjusting for study dropouts due to adverse events. Results Seventeen studies comprised of 5, 975 subjects, totaling 38 active trial arms evaluating 7 drugs, and 17 drug‐dosing combinations met inclusion criteria. Mean pain reduction over placebo ranked highest for duloxetine 120 mg (1.17 95% CI 0.77, 1.58) and pregabalin 600 mg (1.11 95% CI 0.77, 1.45). The Indirect treatment comparison showed largest effect size for duloxetine at 120 and 60 mg followed by pregabalin 600 mg. Conclusions Pregabalin and duloxetine had the largest beneficial effects for chronic peripheral neuropathic pain. In the absence of head‐to‐head trials, meta‐analysis and indirect treatment comparisons inform best practice clinical decision‐making.